Long-Term Effects of Hypoxia-Reoxygenation on Thioredoxins in Rat Central Nervous System - Otero-Losada, Matilde; L, Canepa; Udovin, Lucas; Kobiec, Tamara; Toro-Urrego, Nicolás; A., Kölliker-Frers R.; Capani, Francisco (Current Pharmaceutical Design, 2019)
Background: Oxidative stress induced by the oxidative pathway dysregulation following ischemia/ reperfusion has been proposed as an important cause of neuronal death and brain damage. The proteins of the thioredoxin (Trx) family are crucial mediators of protein function regulating the intracellular hydrogen peroxide levels and redox-sensitive post-translational protein changes. Aim: To analyze the expression and distribution of fourteen members of the Trx family, potentially essential for the regeneration upon long-term brain damage, in a perinatal hypoxia-ischemia rat model induced by common carotid artery ligation. Methods: The right common carotid artery (CCA) was exposed by an incision on the right side of the neck, isolated from nerve and vein, and permanently ligated. Sham-surgery rats underwent right CCA surgical exposure but no ligation. Euthanasia was administered to all rats at 30, 60, and 90 days of age. Protein expression and distribution of fourteen members of the Trx family and related proteins (Grx1, Grx2, Grx3, Grx5, Prx1, Prx2, Prx3, Prx4, Prx5, Prx6, Trx1, Trx2, TrxR1, TrxR2) was examined in the most hypoxia susceptible rat brain areas, namely, cerebellum, corpus striatum, and the hippocampus. Results: The thioredoxin proteins displayed a complex, cell-type, and tissue-specific expression pattern following ischemia/reperfusion. Even 60 days after ischemia/reperfusion, Western blot analysis showed a persistent expression of Trx1 and Grx2 in several brain areas. Conclusion: The Trx family of proteins might contribute to long-term survival and recovery supporting their therapeutic use to curtail ischemic brain oxidative damage following an ischemia/reperfusion insult. Characterization of ischemia/reperfusion oxidative brain damage and analysis of the involved mechanisms are required to understand the underneath processes triggered by ischemia/reperfusion and to what extent and in what way thioredoxins contribute to recovery from brain hypoxic stress.
Keywords: hypoxia-ischemia